The doorman : a novel - Pavone, Chris (MCD/Farrar, Straus and Giroux, 2025)
"Chicky Diaz is everyone's favorite doorman at the Bohemia, the most famous apartment house in the world, home of celebrities, financiers, and New York's cultural elite. Up in the penthouse, Emily Longworth seems to have the perfect everything, all except her husband, whom she'd quietly loathed even before the recent revelations about where the money comes from. But his wealth is immense, their prenup is ironclad, and Emily can't bring herself to leave him. Yet. Downstairs in 2A, Julian Sonnenberg has just received a devastating phone call. He's getting the distinct sense that his cosmopolitan career in the art world is hurtling to an end and that he's just not that useful to anyone anymore. Meanwhile, gathered in the Bohemia's bowels, the building's working-class staff is taking in news that just a few miles uptown, a Black man has been killed by the police, leading to a demonstration, a counterdemonstration, and a long night of violence across the tinderbox city. As Chicky changes into his uniform for tonight's shift, he finds himself breaking a cardinal rule of the job: tonight, he'll be carrying a gun, bought only hours earlier, before he had any idea what's about to happen at the Bohemia. Tonight in the city, enemies will clash, loyalties will be tested, secrets will be revealed--and lives will be lost"--